A new goanna lizard allied with Varanus glauerti from northern Australia - Bedford, Gavin S.; Donnellan, Stephen C. (Zootaxa, 2026)
Here we describe a species from the subgenus Odatria that is allied with the Kimberley Rock Goanna, Varanus glauerti. The new species, Varanus fyfei sp. nov., is highly distinct from V. glauerti in nuclear and mitochondrial phylogenetic analyses and can be morphologically diagnosed on dorsal and tail colour patterns. The new species appears to be a short-range endemic restricted primarily to sandstone ranges and isolated hills of the north-western Northern Territory. It is mostly saxicoline inhabiting sheer rock faces in gorges and utilises horizontal crevices fractionally wider than their head depth on the rock face and at least 2m above ground level as night-time refugia. The species forages diurnally for small lizards and insects on vertical rock-faces. We also demonstrate two evolutionary lineages within V. glauerti, from the east and west Kimberley. The lineages can be distinguished in nuclear and mitochondrial phylogenetic analyses and on dorsal and tail colour patterns and body size. One of our west Kimberley samples is a hybrid, but the ranges of both lineages in the central Kimberley need further definition to better understand the degree of gene flow between the two and typotypic material of V. glauerti Mertens needs examination to establish the taxonomic provenance of the type, which is in poor condition.